The Effect of Virotherapy, Chemotherapy, and Immunotherapy to Immune System: Mathematical Modelling Approach - Sa'adah, Aminatus; Prihantini, Prihantini; Masulah, Bidayatul (KUBIK, 2023)
Medical research and therapeutic interventions continue to evolve, and one interesting area of study is the complex interaction among virotherapy, chemotherapy, and the immune system. Each treatment has its own advantages and disadvantages. In this study, a mathematical model was developed to describe how the immune system, tumor cells, and normal cells interact when all three types of therapy are used to treat cancer patients. To determine the effectiveness of various treatments, numerical simulations of eight different treatment strategies were performed. These simulations measured how much the concentration of immune cells, tumor cells, and normal cells decreased as a result of the treatment. Based on the numerical simulations performed, the application of the three types of therapy provided the greatest reduction (99%) in the concentration of tumour cells but also provided a significant reduction (68%) in the concentration of immune cells in the body.